Audiovisual Media Health Education on Family Behavior in Caring for Tuberculosis Patients - Komang Ayu Henny Achjar; Ni Made Arisasmita Candra Dewi; Agus Sri Lestari; I Ketut Gama; I Gusti Ketut Ngurah; Nyoman Ribek (Journal of Education Reseach and Evaluation, 2024)
Currently, TBC is still a health problem in Indonesian society. It is hoped that the role of the family in assisting tuberculosis patients can help achieve a cure rate so that a reduction in the number of tuberculosis sufferers can be achieved. This research aims to analyze the influence of audiovisual health education media on family behaviour in caring for tuberculosis patients. This type of research is a pre-experimental design with a one-group pretest-posttest design. The population in this study was 75 people. The sampling technique was non-probability with a purposive sampling technique, and a total sample of 63 samples was obtained. The data collection method uses tests. The research instrument used in this research was a questionnaire. Data analysis was carried out using the Wilcoxon test. The results of statistical tests prove that audiovisual health media education influences family behaviour in caring for tuberculosis patients. It was concluded that audiovisual health media education can improve family behaviour in caring for tuberculosis patients. This research implies that the application of audiovisual health media can help families in caring for tuberculosis patients.